Computational Exploration on the Structural and Optical Properties of Gold-Doped Alkaline-Earth Magnesium AuMgn (n = 2–12) Nanoclusters: DFT Study - Zhu, Ben-Chao; Deng, Ping-Ji; Guo, Jia; Kang, Wen-Bin (Frontiers in Chemistry, 2022)
Using CALYPSO crystal search software, the structural growth mechanism, relative stability, charge transfer, chemical bonding and optical properties of AuMgn (n=2-12) nanoclusters were extensively investigated based on DFT. The shape development uncovers two interesting properties of AuMgn nanoclusters contrasted with other doped Mg-based groups, in particular, the planar design of AuMg3 and the highly symmetrical cage-like of AuMg9. The relative stability study shows that AuMg10 has the robust local stability, followed by AuMg9. In all nanoclusters, the charge is transferred from the Mg atoms to the Au atoms. Chemical bonding properties were confirmed by ELF analysis that Mg-Mg formed covalent bonds in nanoclusters larger than AuMg3. Static polarizability and hyperpolarizability calculations strongly suggest that AuMg9 nanocluster possesses interesting nonlinear optical properties. Boltzmann distribution weighted average IR and Raman spectroscopy studies at room temperature verify that these nanoclusters are identifiable by spectroscopic experiments. Finally, the average bond distance and average nearest neighbor distance were fully investigated.